A Rare Cutaneous Tumor With Unusual Dermoscopic Features - Antonio Di Guardo; Luca Gargano; Andrea Ascione; Domenico Giordano; Flavia Persechino; Severino Persechino (Clinical Case Reports)
ABSTRACT Although subtle, dermoscopic clues such as milia‐like cysts, white structureless areas, and peripheral vessels may suggest a biphasic adnexal tumor. Histopathology remains essential for definitive diagnosis. Complete excision with clear margins is typically curative. Rare tumors like CS may benefit from AI‐driven tools to improve preoperative recognition.